Discovery of the subfamily Rhopalomutillinae (Hymenoptera: Mutillidae) in China and description of Pherotilla brothersi sp. nov. - Zhou, Hu-Ting; Lelej, Arkady S.; Xu, Zai-Fu (Zootaxa, 2017)
The subfamily Rhopalomutillinae of the family Mutillidae, represented by the genus Pherotilla Brothers, 2015, is newly recorded from China. Pherotilla brothersi Zhou, Lelej & Xu, sp. nov. (China: Yunnan) is described and illustrated. A key to the Oriental species of Pherotilla is given.